Biocultural Hysteresis Inhibits Adaptation to Environmental Change. (September 2019) - Lyver, P.O'B.; Timoti, P.; Davis, T.; Tylianakis, J.M.
Abstract : Indigenous peoples and local communities (IPLC) often use natural resources as both a reason and mechanism for environmental management, yet a number of environmental, social, and economic drivers disrupt this relationship. Here, we argue that these drivers can also trigger a set of feedback mechanisms that further diminish the efficacy of local management. We call this process biocultural hysteresis. These feedbacks, which include knowledge loss and a breakdown of social hierarchies, prevent IPLC from adapting their management to change. Biocultural hysteresis worsens as IPLC spend an increasing amount of time outside their social–ecological context. Therefore, we argue for adaptive policies and processes that favour protecting and enabling IPLC engagement with their environment. Highlights: As environmental conditions deteriorate, conservation policy frequently limits the engagement of IPLCs with their environments through resource use. Even if these restrictions are intended to be short-term measures, the period of reduced engagement by IPLCs with their environment can have irreversible consequences, such as loss of knowledge or the breakdown of power structures, which prevent culturally appropriate management from resuming or adapting to current conditions when restrictions are lifted. Indigenous knowledge and culturally appropriate management practices can bring significant environmental benefits, but these benefits are threatened when IPLCs are prevented from engaging with their environments, even temporarily.